A review of the relationship between pain, fear avoidance beliefs, and postural stability in subjects with non-specific chronic low back pain - Abdolkarim Karimi; Marzieh Saeidi (Vesnu Publications, 2013)
Introduction: Low back pain (LBP) is one of the most prevalent musculoskeletal disorders in both developed and developing countries. LBP affects 70% to 80% of adults at some time in their lives. Recent evidence suggests that psychosocial factors especially fear avoidance beliefs (FAB) have a critical role to predict disease progression from an acute to a chronic stage as well as the failure of intervention. The aim of this study was to review the relationship between pain, fear avoidance beliefs and postural stability in subjects with non specific chronic low back pain (CLBP). Materials and Methods: In this narrative research, two databases (pub med and Medline) were searched using key words such as chronic low back pain, fear avoidance beliefs, posture, stability, balance, motor control, center of pressure, and force plate. The inclusion criteria was being related to FAB and postural stability and adults with non specific CLBP, in English language, up to 2011, by the format of cohort and cross sectional studies. Results: The results showed that psychological factors like FAB influence the chronicity factor of LBP but the relationship between pain and postural stability was different in these studies. The only study on relationship between postural stability and FAB did not find any significant relationship. Conclusion: It seems that the different results of these studies are due to different methods of data collection. More exact studies are needed for evaluating the relationship between FAB and postural control. Keywords: Chronic low back pain, Fear avoidance beliefs, Stability, Motor control